ZONASI PALEONTOLOGI CEKUNGAN KUTAI BAGIAN BAWAH, DAERAH BALIKPAPAN DAN SEKITARNYA, PROVINSI KALIMANTAN TIMUR - -, Yuyun Yuniardi; -, Rahmat Fakhrudin; -, Lia Jurnaliah (Bulletin of Scientific Contribution, 2010)
Fossil of Foraminifera, Nannoplankton, and Pollen were got into rock sample in lower Kutai Basyn and very interesting to do research. Paleontology zone were made for deliniation of rocks formation in lower Kutai Basyn. Paleontology zone divided into three part : Foraminifera zone, Pollen zone, and Nannoplankton zone.